Increased DNA strand breaks in mononuclear cells from patients with rheumatoid arthritis. Issue 1 (January 1992) - Bhusate, L L; Herbert, K E; Scott, D L; Perrett, D
Abstract : Immune dysfunction is linked with lymphocyte DNA metabolism. In particular, DNA damage may impair lymphocyte function and induce increased cell turnover; such changes are of relevance to the pathogenesis of rheumatoid arthritis. The rate of DNA unwinding in alkaline solution was used as a measure of the number of DNA strand breaks in mononuclear cells freshly isolated from peripheral blood. The rate of DNA unwinding was significantly increased in cells from patients with rheumatoid arthritis compared with those from healthy subjects and from patients with other autoimmune and connective tissue diseases. These findings support the hypothesis that DNA damage is increased in patients with rheumatoid arthritis and it is one factor contributing to immune dysfunction in this disease.